The Effect of Audit Tenure, Audit Delay and Financial Distress on Audit Quality in Manufacturing and Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2018-2022 Period - Maulitya Cucunabila; Sekar Mayangsari (CV. Publikasi Indonesia, 2024)
In the business sector, quality audits are crucial for ensuring accountability and transparency in an organization's financial statements. In the Indonesian setting, businesses that are listed on the Indonesia Stock Exchange (IDX) must prepare financial statements that undergo auditing by a Public Accounting Firm (KAP) to guarantee that fraud and serious errors are not included in the reports. The purpose of this audit is to give stakeholders assurance about the Company's financial standing. The purpose of this study is to evaluate how audit tenure, audit delay, and financial crisis affect the caliber of audits performed on property and real estate, manufacturing, and enterprises listed on the Indonesia Stock Exchange between 2018 and 2022. A quantitative research methodology is used in this investigation. Purposive sampling was employed to select 100 data points for the sample. The Indonesia Stock Exchange and the company's websites are the sources of the data used. This study demonstrates that audit quality is unaffected by audit tenure or audit delay. From 2018 to 2022, the quality of audits in manufacturing and property & real estate companies listed on the Indonesia Stock Exchange was significantly impacted by financial difficulty.